Religion, Forgiveness, Hostility and Health: A Structural Equation Analysis - Lutjen, Laura J. (Journal of religion and health, 2012)
Religious participation has been shown to increase certain factors thought to be protective of health, including social support and positive health habits. The current study considers whether religious participation may likewise have a positive influence on health by increasing forgiveness and diminishing hostility. A structural equation analysis of data collected from a national survey of 1,629 participants supported the hypothesized model that (a) religiosity is related to greater forgiveness, (b) greater forgiveness, in turn, is related to reduced hostility and finally, (c) reduced hostility is related to better subjective health.